Origin and distribution of trace elements in the campus dust of Xi'an, China. Issue 1 (7th February 2019) - Chen, Hao; Lu, Xinwei
Abstract: The concentrations of As, Ba, Co, Cr, Cu, Mn, Ni, Pb, V, and Zn in dust samples from kindergartens, primary schools, secondary schools, and universities in Xi'an City have been determined by X-ray fluorescence spectrometry. The element concentrations in dust samples collected from the campuses were higher than background levels, in particular for Pb, Zn, Cr, Cu, Co, and Ba. Summary statistics and enrichment factors allowed for the differentiation between contributions from local soil and from anthropogenic sources. The results of a multivariate spatial correlation-principal component analysis demonstrated that metal concentrations could be related to natural and anthropogenic sources separately and in combination. Source apportionment based on multiple linear regression indicated that 67% of the trace elements could be ascribed to natural and traffic sources, 13% to industrial sources, 19% to construction activities, and an additional 1% to traffic and industrial sources.